2017
DOI: 10.2147/dddt.s133020
|View full text |Cite
|
Sign up to set email alerts
|

Atorvastatin, a double weapon in osteoporosis treatment: an experimental and clinical study

Abstract: ObjectiveThe aim of this study was to evaluate the effect of atorvastatin on the bone formation and resorption markers in ovariectomized rats (experimental study), and to study its effect on the bone mineral density (BMD) in postmenopausal osteoporotic women (clinical study).Materials and methodsThe study involved experimental and clinical aspects. In the experimental aspect, 42 female Wistar rats were divided into five groups: Group I (n=6; sham-operated), Group II (n=6; 1 mL of carboxymethyl cellulose [CMC] … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 48 publications
2
10
0
Order By: Relevance
“…Interestingly, several studies have now indicated that post-menopausal women taking cholesterol lowering drugs such as statins (HMGCoA reductase inhibitors) have better bone health [42, 43]. Furthermore, elevated cholesterol is a recognized risk factor for osteoporosis in post-menopausal women [4448].…”
Section: The Importance Of 27hc In Bone Healthmentioning
confidence: 99%
“…Interestingly, several studies have now indicated that post-menopausal women taking cholesterol lowering drugs such as statins (HMGCoA reductase inhibitors) have better bone health [42, 43]. Furthermore, elevated cholesterol is a recognized risk factor for osteoporosis in post-menopausal women [4448].…”
Section: The Importance Of 27hc In Bone Healthmentioning
confidence: 99%
“…Moreover, the levels of biochemical markers, including osteocalcin (OC), alkaline phosphatase (ALP), and deoxypyridinoline (DPD), in the OVX group were significantly higher than those in the sham group. In OVX group, serum ALP levels, which are a bone turnover marker, and OC levels, which are a bone formation marker, were significantly elevated [30]. The body weight, as well as OC, ALP, and DPD levels, significantly decreased in the SCE-treated group compared with those in the OVX group.…”
Section: Effect Of Sce On Body Weight and Serum Biochemistrymentioning
confidence: 86%
“…The levels of serum biomarkers of ALP and osteocalcin in the OVX rats that received PBS or free NONOate were significantly higher than those in the healthy control rats (Figure e, P < 0.05), owing to compensation for increased bone turnover . However, the OVX‐induced increases in ALP and osteocalcin were significantly suppressed by treatment with MPs ( P < 0.05).…”
mentioning
confidence: 92%